(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2026)
This study investigates the role of the Superior Court of Justice (STJ) and the Federal Supreme Court (STF) in the environmental litigation arising from the collapse of the Córrego do Feijão mine dam in Brumadinho/MG, Brazil, in 2019. The objective is to identify the legal criteria applied by the Superior Courts in the decisions rendered in the case — particularly regarding jurisdiction, compensation parameters and the participation of victims in redress proceedings — in order to understand their possible impacts on environmental case law. To this end, the study first presents the main factors involved in the disaster and its socio-environmental and legal repercussions, drawing on disaster law and environmental civil liability doctrine. It then analyzes the redress measures adopted and the decisions of the Superior Courts on the matter. The research methodology is qualitative and descriptive, adopting the deductive method, with data collection based on bibliographic and documentary research. The hypothesis is that the decisions of the Superior Courts establish interpretative criteria that tend to influence both the accountability of those involved and the configuration of damage redress instruments in future disasters. The hypothesis was partially confirmed: although the decisions examined set relevant criteria – such as the jurisdiction of the Federal Courts over the criminal case and the individual enforceability of liquidated clauses of the conduct adjustment agreement (TAC) – central questions remain open, such as the application of the Consumer Protection Code to the victims, submitted to the repetitive appeals procedure (Topic 1280) and still pending judgment. It is concluded that the effectiveness of judicial protection remains dependent on procedures that ensure not only the formal accountability of those involved, but also effective mechanisms for enforcing compensatory measures and for the participation of those affected.